Designing and optimising anaerobic digestion systems: A multi-objective non-linear goal programming approach - Nixon, J.D. (Energy (Oxford), 2016)
This paper presents a method for optimising the design parameters of an anaerobic digestion (AD) system by using first-order kinetics and multi-objective non-linear goal programming. A model is outlined that determines the ideal operating tank temperature and hydraulic retention time, based on objectives for minimising levelised cost of electricity, and maximising energy potential and feedstock mass reduction. The model is demonstrated for a continuously stirred tank reactor processing food waste in two case study locations. These locations are used to investigate the influence of different environmental and economic climates on optimal conditions. A sensitivity analysis is performed to further examine the variation in optimal results for different financial assumptions and objective weightings. The results identify the conditions for the preferred tank temperature to be in the psychrophilic, mesophilic or thermophilic range. For a tank temperature of 35 °C, ideal hydraulic retention times, in terms of achieving a minimum levelised electricity cost, were found to range from 29.9 to 33 days. Whilst there is a need for more detailed information on rate constants for use in first-order models, multi-objective optimisation modelling is considered to be a promising option for AD design. •Nonlinear goal programming is used to optimise anaerobic digestion systems.•Multiple objectives are set including minimising the levelised cost of electricity.•A model is developed and applied to case studies for the UK and India.•Optimal decisions are made for tank temperature and retention time.•A sensitivity analysis is carried out to investigate different model objectives.